Seminar Parenting sebagai Upaya Peningkatan Pemahaman Kesehatan Mental Ibu dan Anak di Desa Pegagan - As Syifa Sidikah Thayibatunisa; Ganis Ainnur Rahmah; Anindia Nabillah Nurafifah; Royhan Azizy; Sandi Pratama; Syamsul Mubarok; Sandinata Kusuma (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
A parenting seminar on maternal and child mental health organized by KPM UI Bunga Bangsa Cirebon students in Pegagan Village is a form of community service aimed at raising awareness and understanding of the importance of mental health in parenting. The limited knowledge of mental health issues in rural communities, coupled with high levels of stress experienced by parents, often negatively impacts parenting practices. This has the potential to hinder optimal child development, both physically, psychologically, and socially. Therefore, this activity was designed with a participatory approach, where the community is not merely an object but is also involved from the beginning of the planning process. This process includes coordination with village officials, seminars, and monitoring and evaluation stages, so that the community feels ownership and plays an active role in the program. The seminar featured speakers from psychology and legal academics who explained the relationship between parental mental health and fulfilling legal obligations to protect children's rights. The material presented emphasized how parental stress and emotions can affect child development, as well as the importance of parents' ability to manage the pressures of everyday life. Participants gained an understanding of strategies for maintaining mental health, including good time management, building open communication within the family environment, and strengthening social support as an emotional support system. The results of the activity showed an increase in participants' awareness of the importance of mental health not only as an individual need, but also as a moral, social, and legal responsibility in creating a healthy, safe, and resilient family environment. Therefore, this parenting seminar can be seen as an effective educational strategy, not only strengthening parents' capacity to raise children but also building sustainable local support networks for the well-being of families and communities.